A Review of the Academic and Psychological Impact of the Transition to Secondary Education - Evans, Danielle; Borriello, Giulia A.; Field, Andy P. (Frontiers in Psychology, 2018)
The transition from primary to secondary education is one of the most stressful events in a young person’s life (Zeedyk et al., 2003) and can have a negative impact on psychological wellbeing and academic achievement. One explanation for these negative impacts is that the transition coincides with early adolescence, a period during which certain psychological disorders (i.e., anxiety disorders) become more salient (Kessler et al., 2005) and marked social, biological, and psychological development occurs (Anderson, Jacobs, Schramm, & Splittgerber, 2000). This review evaluates the existing literature on the psychological and academic impacts of the transition to secondary education on young adolescents. We examine the factors that plausibly increase or mitigate the risk of developing mental health issues and/or a decline in academic performance during the transition to secondary education. We also review the interplay between psychological health and academic achievement across and beyond the transition. We conclude with a summary of what schools and parents can learn from these findings to support children in a successful transition into secondary education.